Effect of Organoclay Content and Molecular Weight on Cellulose Acetate Nanocomposites Properties - Guarda-Moraga, A; Rodriguez-Mercado, F; Bruna-Bugueno, J; Galotto-Lopez, M (2012)
Sin Editorial Disponible